Total polyphenols from Syzygium cumini (L.) Skeels fruit extract - Migliato, Ketylin Fernanda [UNESP]; De Carvalho, Elisângela Simões [UNESP]; Do Sacramento, Luis Vitor Silva [UNESP]; De Mello, João Carlos Palazzo; Baby, André Rolim; Velasco, Maria Valéria Robles; Salgado, Hérida Regina Nunes [UNESP] (My University, 2009)
A precise, accurate and low cost spectrophotometric method was developed and validated for routine determination of total polyphenols, as pyrogallic acid equivalents, from the percolated and lyophilized extract of Syzygium cumini (L.) Skeels fruits. Validation was assessed experimentally and data were rigorously treated by statistical analysis. Analytical parameters were: linearity, interval (range), precision and recovery/accuracy, limit of detection (LOD, μg mL -1) and limit of quantification (LOQ, μg mL -1). The visible spectrophotometric method presented linearity (r 2 = 0.9979 ± 0.0010) over the concentration range 0.25-7.5 μg mL -1 of standard pyrogallic acid, precision ≤ 2.918171%, recovery/accuracy ranging from 96.228693 to 107.17701%, LOD = 0.21 μg mL -1 and LOQ = 0.64 μg mL -1.
Keywords: Analytical method validation; Botanical extract; Spectrophotometry; Syzygium cumini; Total polyphenols